PERAN KAIN BROKAT DALAM DESAIN FURNITUR SEBAGAI REPRESENTASI WANITA JAWA - Cantika, Lintang Nur; Setia Monata, Rio; Bayu Ibrahim, Dinullah (ASKARA: Jurnal Seni dan Desain, 2025)
Lace is often associated with elegance and femininity, chosen as the primary material to create a connection between furniture design art and cultural symbolism. Through historical and cultural analysis, this research identifies how lace has become an essential part of Javanese women's identity and how these elements can be translated into simple and functional furniture designs. The research methods involve literature studies and practical experiments in furniture prototyping. The results show that the use of lace not only adds aesthetic value but also enriches the cultural narrative in furniture design. And then, this research contributes to a deeper understanding of the relationship between traditional textiles and cultural identity in the context of modern furniture design.